RETRACTED: Analysis of the street network of cities of Krasnodar region, Russia - Daisheva Almira; Kuzyakina Marina; Pelina Alina; Doumit Jean; Gura Dmitry (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001